Hesperetin suppresses RANKL‐induced osteoclastogenesis and ameliorates lipopolysaccharide‐induced bone loss. Issue 7 (11th December 2018) - Liu, Hui; Dong, Yonghui; Gao, Yutong; Zhao, Liming; Cai, Cong; Qi, Dahu; Zhu, Meipeng; Zhao, Libo; Liu, Changyu; Guo, Fengjing; Xiao, Jun; Huang, Hui
Abstract: Destructive bone diseases caused by osteolysis are increasing in incidence. They are characterized by an excessive imbalance of osteoclast formation and activation. During osteolysis, the activation of nuclear factor‐κB (NF‐κB) and mitogen‐activated protein kinase (MAPK) signaling pathways are triggered by receptor activator of NF‐κB ligand (RANKL), inflammatory factors, and oxidative stress. Previous studies have indicated that the common flavanone glycoside compound hesperetin exhibits anti‐inflammatory and antioxidant activity by inhibition of NF‐κB and MAPK signaling pathways. However, the direct relationship between hesperetin and osteolysis remain unclear. In the present study, we investigated the effects of hesperetin on lipopolysaccharide (LPS)‐induced osteoporosis and elucidated the related mechanisms. Hesperetin effectively suppressed RANKL‐induced osteoclastogenesis, osteoclastic bone resorption, and F‐actin ring formation in a dose‐dependent manner. It also significantly suppressed the expression of osteoclast‐specific markers including tartrate‐resistant acid phosphatase, matrix metalloproteinase‐9, cathepsin K, c‐Fos, and nuclear factor of activated T‐cells cytoplasmic 1. Furthermore, it inhibited osteoclastogenesis by inhibiting activation of NF‐κB and MAPK signaling, scavenging reactive oxygen species, and activating the nuclear factor E2 p45‐related factor 2/heme oxygenase 1 (Nrf2/HO‐1) signaling pathway. Consistent with in vitro results, hesperetin effectively ameliorated LPS‐induced bone loss, reduced osteoclast numbers, and decreased the RANKL/OPG ratio in vivo. As such, our results suggest that hesperetin may be a great candidate for developing a novel drug for destructive bone diseases such as periodontal disease, tumor bone metastasis, rheumatoid arthritis, and osteoporosis. Abstract : Hesperetin suppresses receptor activator of NF‐κB ligand (RANKL)‐induced osteoclast differentiation and bone resorption through repressing the activity of the nuclear factor‐κB (NF‐κB) and mitogen‐activated protein kinases (MAPKs) signaling pathways and activating the Nrf2/HO‐1 signaling pathways.